Method for improving plasticity by refining grains and exciting twin crystal effect of cast titanium alloy

By refining the grains, combined with cold crucible suspension smelting, centrifugal casting and thermal isostatic pressure treatment, the twinning effect of titanium alloy is stimulated, and the problem of low plasticity of titanium alloy is solved, achieving high strength and high plasticity of the material.

CN119640176AActive Publication Date: 2025-03-18NORTHWESTERN POLYTECHNICAL UNIV
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411969040.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-18
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The grain combination of cast titanium alloys is coarse and difficult to regulate through the post-treatment process, resulting in low plasticity and a decrease of 40% to 50% compared to the deformed alloy.

Method used

By refining the grains, a casting method combining cold crucible suspension smelting and centrifugal casting is adopted, combined with thermal isostatic pressure treatment, the twins during deformation are stimulated, and the tensile strength and plasticity are improved.

Benefits of technology

The plasticity of cast titanium alloy is significantly improved, and the elongation of ZTC4 reaches more than 15%, while maintaining the strength of the material, making it simple to operate and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640176A_ABST
    Figure CN119640176A_ABST
Patent Text Reader

Abstract

The invention provides a method for improving plasticity by refining grains to excite a twin crystal effect of a cast titanium alloy, and relates to the technical field of cast titanium alloy structure property regulation and control, the method comprises the following steps: step 1, mixing materials according to titanium alloy nominal components, and smelting in a vacuum consumable electric arc furnace to obtain a primary ingot; 2, the primary ingot obtained in the step 1 is subjected to centrifugal casting under the conditions that the centrifugal rotating speed ranges from 150 r / min to 300 r / min and the mold shell preheating temperature ranges from 200 DEG C to 300 DEG C through cold crucible suspension smelting, rod-shaped samples are obtained and discharged out of a furnace after being cooled, and a casting system adopted in the casting process needs to guarantee that the rod-shaped samples are distributed at intervals; and 3, carrying out hot isostatic pressing on the rod-shaped sample obtained in the step 2 at 920 DEG C / 130 MPa for 3 hours, and carrying out furnace cooling. By means of the pouring method, cast titanium alloy grains can be refined, deformation twin crystals can be induced to be generated, the plasticity of the cast titanium alloy is remarkably improved, and the ZTC4 elongation reaches 15% or above. The method is easy to operate and low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of structure and performance regulation of cast titanium alloys, and in particular to a method for improving plasticity by stimulating twinning effect of cast titanium alloys through grain refinement. Background Art

[0002] Titanium alloy castings have been widely used in aerospace, marine engineering, shipbuilding, petrochemical and other fields due to their low density, high specific strength, excellent corrosion resistance and relatively low processing cost. Among them, ZTC4 (Ti-6Al-4V) alloy has good comprehensive mechanical properties and excellent casting properties, and is the most widely used cast titanium alloy. However, due to the coarse composition of cast titanium alloys and the difficulty in regulating through post-processing processes, the strength of titanium castings is not much different from that of deformed alloys with the same composition, but the plasticity is reduced by about 40%~50%.

[0003] Some documents mentioned that the problems of coarse structure, stress concentration and poor plasticity of titanium alloy components can be improved by secondary processing such as additive manufacturing on the original casting matrix, thereby improving the elongation of alloy castings. However, this secondary processing method is complex and costly. Some other documents also mentioned that the refinement of titanium alloy structure can be achieved by controlling the solidification path. Compared with the method of adding refiners to refine the grains, it is not easy to introduce foreign inclusions, and there is no problem of performance deterioration caused by foreign inclusions. The disadvantage is that this method requires insulation in a certain temperature zone during the solidification of the molten metal, and the temperature control accuracy is difficult to control. Summary of the invention

[0004] In view of the above technical problems, the present invention proposes a method for improving plasticity by refining the grains to stimulate the twinning effect of cast titanium alloy, which specifically includes a casting method, a hot isostatic pressing process and a casting model design. Through the method of the present invention, the grains of cast titanium alloy can be refined, twins in the deformation process can be stimulated, and the tensile strength can be improved while significantly improving the plasticity of cast titanium alloy, and the ZTC4 elongation can reach more than 15%.

[0005] To achieve the above object, the present invention adopts the following technical solution: The present invention provides a method for improving plasticity of a cast titanium alloy by stimulating a twinning effect through grain refinement, comprising the following steps: Step 1: Mix materials according to the nominal composition of titanium alloy, and melt them in a vacuum consumable arc furnace to obtain a primary ingot; Step 2: The primary ingot obtained in step 1 is melted by cold crucible suspension melting, and a rod-shaped sample is cast by centrifugal casting, and the rod-shaped sample is taken out of the furnace after cooling; Step 3: The rod-shaped sample obtained in step 2 is subjected to hot isostatic pressing and then cooled in the furnace.

[0006] As a further illustration of the present invention, the pouring process in step 2 adopts a centrifugal pouring method, and the specific parameters are: centrifugal speed 150~300 r / min, mold shell preheating temperature 200~300℃.

[0007] As a further illustration of the present invention, the pouring system used in the pouring process in step 2 needs to ensure that the rod-shaped samples are distributed at intervals.

[0008] As a further explanation of the present invention, the pouring system used in the pouring process in step 2 includes a pouring cup, a straight runner, a cross runner and a rod-shaped specimen; wherein the cross runner consists of an upper cross runner and a lower cross runner, both of which adopt a 60° cross-distribution structural design, the straight runner is located at the center of the cross runner and distributed from top to bottom, the top of the straight runner extends to above the upper cross runner and is connected to the pouring cup, the bottom extends to below the lower cross runner and has a hemispherical straight runner socket, and the rod-shaped specimens are spaced between the upper cross runner and the lower cross runner.

[0009] As a further illustration of the present invention, the cross-sectional size of the runner is 25x20 mm; the diameter of the sprue is 50 mm; the diameter of the rod-shaped specimen is 14 mm, the length is 140 mm, and the spacing between the specimens is 7 mm.

[0010] As a further illustration of the present invention, the specific process conditions of the hot isostatic pressing treatment are hot isostatic pressing at 920°C / 130MPa for 3h.

[0011] Compared with the prior art, the present invention has the following beneficial technical effects: The pouring method of the present invention can refine the grains of the cast titanium alloy, induce the generation of deformation twins, significantly improve the plasticity of the cast titanium alloy, and achieve a ZTC4 elongation of more than 15%. The method is simple to operate and has low cost.

[0012] Other features and advantages of the technical solution will be described in the subsequent description, and partly become apparent from the description, or understood by implementing the technical solution. The purpose and other advantages of the technical solution can be achieved and obtained through the structures specifically pointed out in the written description and the drawings.

[0013] The technical solution of the present technical solution is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] The accompanying drawings are used to provide a further understanding of the technical solution and constitute a part of the specification. Together with the embodiments of the technical solution, they are used to explain the technical solution and do not constitute a limitation of the technical solution. In the accompanying drawings: Figure 1 It is a schematic diagram of the structure of the pouring system of the present invention.

[0015] Figure 2 Schematic diagram of the size of tissue slice clusters according to an embodiment of the present invention.

[0016] Figure 3 It is a tensile curve diagram of the alloy engineering stress-engineering strain of an embodiment of the present invention.

[0017] Figure 4 This is the alloy deformation structure of the embodiment of the present invention.

[0018] Figure 5 This is a schematic diagram of the tissue sheet size of Comparative Example 1.

[0019] Figure 6 This is the engineering stress-engineering strain tensile curve of the alloy of Comparative Example 1.

[0020] Figure 7 This is a schematic diagram of the pouring system structure of Comparative Example 2.

[0021] Figure 8 This is a schematic diagram of the tissue sheet size of Comparative Example 2. DETAILED DESCRIPTION

[0022] The preferred embodiments of the present technical solution are described below in conjunction with the accompanying drawings. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present technical solution, and are not used to limit the present technical solution.

[0023] The present invention provides a method for improving plasticity of a cast titanium alloy by stimulating a twinning effect through grain refinement, comprising the following steps: Step 1: Mix the materials according to the nominal composition of the titanium alloy, and melt them in a vacuum consumable arc furnace to obtain a primary ingot.

[0024] Step 2: The primary ingot obtained in step 1 is melted by cold crucible suspension melting, and a rod-shaped sample is cast by centrifugal casting, and the rod-shaped sample is taken out of the furnace after cooling.

[0025] In step 2, the smelting equipment is a cold crucible suspension smelting furnace. Since suspension smelting is a non-contact state smelting, it reduces inclusions and improves the superheat and uniformity of the melt. At the same time, the cold crucible suspension smelting technology does not require additional stirring equipment. The melt can be fully stirred under the action of electromagnetic force, which is beneficial to improve the component uniformity of the smelting material and reduce pollution.

[0026] Furthermore, in step 2, the pouring process adopts a centrifugal pouring method, and the specific parameters are: centrifugal speed 150~300r / min, mold shell preheating temperature 200~300℃. Centrifugal force can break grains during alloy solidification, which is conducive to grain refinement. Among them, the mold shell adopts a lower preheating temperature, so that the alloy cools faster during the pouring process, which is conducive to grain refinement and promotes the appearance of deformation twins during deformation. Exemplarily, the centrifugal speed can be set to 150 r / min, 200 r / min, 250 r / min, 300 r / min, etc.; the preheating temperature can be set to 300℃, 280℃, 250℃, 230℃, 200℃, etc.

[0027] Furthermore, the pouring system used in the pouring process in step 2 needs to ensure that the rod-shaped specimens are distributed at intervals. Figure 1 As shown, the pouring system includes a pouring cup 1, a sprue 2, a runner 3, and a rod-shaped sample 4; wherein the runner 3 consists of an upper runner 301 and a lower runner 302. Both the upper runner 301 and the lower runner 302 adopt a 60° cross-distribution structure design, and the cross-section size of the runner is 25x20mm. The purpose of the structural design of the runner here is to allow the molten metal to fill the top runner before the casting during the filling process, so as to achieve simultaneous filling of the casting with the upper and lower runners, and also play a supporting and fixing role. The sprue 2 is located at the center of the runner 3 and is distributed from top to bottom. The top of the sprue 2 extends to the top of the upper runner 301 and is connected to the pouring cup 1, and the bottom extends to the bottom of the lower runner 302 and has a hemispherical sprue socket, which can prevent turbulence and splashing and ensure smooth filling. The rod-shaped samples 4 are distributed between the upper runner and the lower runner at intervals. In view of the vacuum consumable melting requirements of titanium-based alloys, the diameter of the sprue is set to 50mm to match the electrode size of the vacuum consumable melting equipment. The diameter of the rod-shaped specimen is set to 14mm, the length is 140mm, and the test rod spacing is 7mm. This specimen spacing ensures smooth filling during centrifugal pouring, while optimizing the temperature gradient during solidification, faster cooling rate, and thus a fine grain effect.

[0028] Step 3: The rod-shaped sample obtained in step 2 is subjected to hot isostatic pressing and then cooled in the furnace.

[0029] The specific process conditions of the hot isostatic pressing treatment are hot isostatic pressing at 920°C / 130MPa for 3h.

[0030] The present invention adopts a larger isostatic pressure to make the material plastic, so that the gaps collapse under the pressure difference, effectively eliminating defects and achieving an effect close to the theoretical density; at the same time, a longer insulation time is adopted, and the material is subjected to high temperature and high pressure for a long enough time during the HIP process to ensure the densification degree of the material.

[0031] The present invention is further described below in conjunction with specific embodiments.

[0032] The mechanical property tests in the following examples and comparative examples refer to "GB / T228.1-2010 Metallic Material Tensile Test Part 1: Room Temperature Test Method". The standard tensile specimen cylindrical test bar is designed with a clamping end and a gauge end. The clamping end is an M10 thread with a length of 15 mm, the gauge section has a diameter of 5 mm and a length of 25 mm, the parallel section has a length of 35 mm, and the connection at each end is a chamfer with a radius of 4 mm and a length of 3 mm. The tensile rate is 0.45 mm / min. Example 1

[0033] 1) Ingredients and electrode pressing: Mix titanium sponge, Al beans, AlV58, and TiO2 powders and melt them in a vacuum consumable arc furnace; 2) centrifugally pouring the primary ingot obtained in step 1 into a cold crucible suspension melting furnace at a centrifugal speed of 200 r / min, a mold shell preheating temperature of 300° C., and a pouring speed of 3 kg / s, and then taking it out of the furnace after cooling; 3) The sample obtained in step 2 was hot isostatically pressed at 920°C / 130MPa for 3h.

[0034] The obtained sample was characterized by EBSD technique, and the size of the lamellae was as follows: Figure 2 ; The chemical composition was analyzed at the National Nonferrous Metals and Electronic Materials Analysis and Testing Center. The main components are as follows: Al: 6.16%, V: 4.06%, Fe: 0.30%; O: 0.12%, and the rest is titanium. The room temperature mechanical properties tested using an electronic universal testing machine are: yield strength 760MPa, tensile strength 831MPa, elongation 16%, and engineering stress-strain curves are as follows: Figure 3 Deformed tissues such as Figure 4 , it can be seen that deformation twins appear in the organization.

[0035] This embodiment achieves microstructure refinement of the cast titanium alloy, induces deformation twins, and increases plasticity to more than 15% while maintaining the strength of the material by designing the pouring method and pouring model during the casting process. The method is simple to operate and has low cost.

[0036] Comparative Example 1 1) Ingredients and electrode pressing: Mix titanium sponge, Al beans, AlV58, and TiO2 powders and melt them in a vacuum consumable arc furnace; 2) gravity pouring the primary ingot obtained in step 1 into a cold crucible suspension melting furnace, and taking it out of the furnace after cooling; 3) The sample obtained in step 2 was hot isostatically pressed at 920°C / 130MPa for 3h.

[0037] The EBSD technique is used to characterize the size of the lamellae. Figure 5; The chemical composition was analyzed at the National Nonferrous Metals and Electronic Materials Analysis and Testing Center. The main components are as follows: Al: 5.95%; V: 4.00%; Fe: 0.30%; O: 0.15%, and the rest is titanium. The room temperature mechanical properties tested using an electronic universal testing machine are: yield strength 759 MPa, tensile strength 801 MPa, elongation 6.5%, and engineering stress-strain curves are as follows: Figure 6 .

[0038] Comparative Example 2 1) Ingredients and electrode pressing: Mix titanium sponge, Al beans, AlV58, and TiO2 powders and melt them in a vacuum consumable arc furnace; 2) The primary ingot obtained in step 1 is centrifugally cast, and the casting system adopts Figure 7 The plum-shaped cast bars shown (there is no spacing between the cast bars) are taken out of the furnace after cooling; 3) The sample obtained in step 2 was hot isostatically pressed at 920°C / 130MPa for 3h.

[0039] The EBSD technique is used to characterize the size of the lamellae. Figure 8 ; Its chemical composition was analyzed at the National Nonferrous Metals and Electronic Materials Analysis and Testing Center, and the mass percentages of the main components were: Al: 5.97%; V: 4.12%; Fe: 0.30%; O: 0.12%, and the rest was titanium.

[0040] From the organization comparison of the attached figure, it can be seen that compared with the coarse organization of the gravity-cast Ti-6Al-4V alloy of Comparative Example 1 and the centrifugally cast plum-shaped cast rod Ti-6Al-4V alloy of Comparative Example 2, the centrifugally cast Ti-6Al-4V alloy using the casting model of the present invention in Example 1 has a finer organization. After the fine-grained organization of Example 1 is stretched and deformed, tensile twins appear in the organization, and the elongation is significantly increased.

[0041] Obviously, those skilled in the art can make various changes and modifications to the technical solution without departing from the spirit and scope of the technical solution. Thus, if these modifications and variations of the technical solution fall within the scope of the claims of the technical solution and their equivalents, the technical solution is also intended to include these modifications and variations.

Claims

1. A method for improving plasticity of a cast titanium alloy by refining grains to stimulate the twinning effect, characterized in that: The steps include: Step 1: Mix materials according to the nominal composition of titanium alloy, and melt them in a vacuum consumable arc furnace to obtain a primary ingot; Step 2: The primary ingot obtained in step 1 is melted by cold crucible suspension melting, and a rod-shaped sample is cast by centrifugal casting, and the rod-shaped sample is taken out of the furnace after cooling; Step 3: The rod-shaped sample obtained in step 2 is subjected to hot isostatic pressing and cooled in the furnace.

2. The method for improving plasticity of a cast titanium alloy by stimulating the twinning effect through grain refinement as claimed in claim 1, characterized in that: The pouring process in step 2 adopts a centrifugal pouring method, and the specific parameters are: centrifugal speed 150~300 r / min, mold shell preheating temperature 200~300℃.

3. The method for improving plasticity of a cast titanium alloy by stimulating the twinning effect through grain refinement as claimed in claim 1, characterized in that: The pouring system used in the pouring process in step 2 must ensure that the rod-shaped specimens are distributed at intervals.

4. The method for improving plasticity of a cast titanium alloy by stimulating the twinning effect through grain refinement as claimed in claim 1, characterized in that: The pouring system used in the pouring process in step 2 includes a pouring cup, a straight runner, a cross runner and a rod-shaped specimen; the cross runner consists of an upper cross runner and a lower cross runner, both of which adopt a 60° cross-distribution structural design, the straight runner is located at the center of the cross runner and distributed from top to bottom, the top of the straight runner extends to above the upper cross runner and is connected to the pouring cup, the bottom extends to below the lower cross runner and has a hemispherical straight runner socket, and the rod-shaped specimens are distributed between the upper cross runner and the lower cross runner.

5. The method for improving plasticity of a cast titanium alloy by stimulating the twinning effect through grain refinement as claimed in claim 4, characterized in that: The cross-sectional dimensions of the runner are 25x20mm; the diameter of the straight runner is 50mm; the diameter of the rod-shaped specimen is 14mm, the length is 140mm, and the spacing between the specimens is 7mm.

6. The method for improving plasticity of a cast titanium alloy by stimulating the twinning effect through grain refinement as claimed in claim 1, characterized in that: The specific process conditions of the hot isostatic pressing treatment are hot isostatic pressing at 920°C / 130MPa for 3h.

Citation Information

Patent Citations

  • Precision forming and casting method of high-volume-fraction titanium-based composite material

    CN111074095A

  • Smelting and pouring method of titanium alloy casting with thin-wall and complex structure

    CN111185573A

  • Manufacturing method of titanium alloy casting

    CN111321306A

  • Gating system for casting alloy standard samples and manufacturing method of mold shell

    CN112317692A

  • Anti-damage high-toughness cast titanium alloy and precision casting method thereof

    CN112831689A